Worldwide Bureaucracy Indicators : Methodology, Insights, and Applications - World Bank (World Bank, Washington, DC, 2021)
What is the appropriate level of employment in the public sector as a whole and for essential workers like public administrators, teachers, and doctors? Is the public sector wage bill affordable? Does the public sector pay competitive wages compared to the private sector to attract talent while not crowding out private sector jobs? Does the public sector pay equal wages to workers in similar jobs and with similar skills? Does the public sector promote gender equality in employment? And are public sector pay and employment practices contributing to higher public sector productivity, better service delivery, and improved governance? The Worldwide Bureaucracy Indicators (WWBI) were developed in response to growing calls to provide more empirical foundation to similar questions on the public workforce. This report sets out to introduce the Indicators estimated from microdata drawn from the labor force and household welfare surveys and augmented with administrative data for 202 economies covering the demographics of the private and public sector workforces, relative wages and premiums, and the public sector wage bill. The report details the methodology used to construct the WWBI, including a description of the data sources and estimations used for the different indicators, presents the main findings emerging from the dataset on core questions, and presents potential policy and research applications of the dataset.